PEMBELAJARAN HATSUON MENGGUNAKAN TEKNIK DIKTE - Jelang Ramadhan; Yuli Wahyuni; M. Ikhwan Al Badar; Maharani Diastari Hartanto; Gita Pramudyarsi Laksita Hapsari (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2022)
Research on Japanese pronunciation skills for Indonesian students is important. This research describes the student’s ability to listen to Japanese pronunciation / Hatsuon using dictation techniques and responses to dictation techniques in learning Japanese pronunciation. This research method uses a descriptive qualitative research instrument in the form of a questionnaire. The respondents in this study were students of the Japanese Language Education study program at the University of Muhammadiyah Yogyakarta, as many as 15 people who had Japanese language skills equivalent to N5. This research showed that almost all students tend to easily listen to long vowels and double consonants and distinguish sounds in the lines SA and SHA and JA and ZA. However, the TSU consonants at the beginning of the word are pretty challenging to catch appropriately. Then from the results of the questionnaire distribution, it can be seen that students think that the dictation technique is an excellent alternative to studying Japanese pronunciation.